A new specimen geometry to determine the through-thickness tensile strength of composite laminates. (August 2015) - Hoffmann, Marco; Zimmermann, Kristian; Bautz, Brian; Middendorf, Peter
Abstract: The tensile strength in thickness direction is one of the dimensioning parameters for composite load introductions, which are exposed to complex three-dimensional stress states, like e.g. composite lugs. In the present paper a simple test setup which introduces the load into the specimen by a form fit was chosen to determine the through-thickness tensile strength of quasi-isotropic carbon/epoxy laminates. By means of detailed finite element analyses a new quadrilaterally waisted specimen geometry was developed and validated by mechanical testing. The influence of the manufacturing process on the location of failure was investigated and recommendations for future tests are made. Compared to alternative state of the art methods the proposed test method leads to higher accuracy and reproducibility of the determined through-thickness tensile strength.